1969
DOI: 10.1111/j.1463-6395.1969.tb00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphomyeloid Tissues, Blood Cells and Plasma Proteins in Chimaera monstrosa (Pisces, Holocephali)

Abstract: The hematocrit of Chimaera monstrosa is very low. Among the blood cells a large proportion are leukocytes. The majority of the leukocytes may be regarded as lymphocytes or lymphocyte‐like cells. Granulocytes constitute only a minor portion of the leukocytes of the blood but are abundant in the connective tissue. From morphological grounds it is probable that lymphocytopoiesis takes place in the spleen, the cranial lymphomyeloid tissue, the thymus and possibly also in other less well defined lymphomyeloid struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…However, in other primitive fishes (Stahl, 1967;Fange and Sundell, 1969;Mattisson and Fange, 1986) in Holocephali (Chandler, 1911;van der Horst, 1925;Tilney, 1927;Vialli, 1932;Scharrer, 1944), in Chondrostei and Holostei, formerly Ganoidei, and in the urodeles Ambystoma (Dempster, 1930) and Megalobatrachus japonicus (Sano and Imai, 19611, lymphohaemopoietic masses occur in association with the meninges and choroid plexuses of various regions of the central nervous system. According to our results, the histological organization of the lymphohaemopoietic tissue found in the meninges of the stingray Dasyatis akajei resembles that reported by light (Stahl, 1967;Fange and Sundell, 1969) and electron microscopy (Mattisson and Fange, 1986) for the cranial lymphoid tissues of holocephalans and for the lymphomyeloid aggregates present in the meninges of the fourth ventricle of ganoids (Chandler, 1911;Scharrer, 1944). In all these locations, a reticular stroma has been recognized where lymphoid cells and developing and mature granulocytes reside and differentiate.…”
Section: Discussionmentioning
confidence: 96%
“…However, in other primitive fishes (Stahl, 1967;Fange and Sundell, 1969;Mattisson and Fange, 1986) in Holocephali (Chandler, 1911;van der Horst, 1925;Tilney, 1927;Vialli, 1932;Scharrer, 1944), in Chondrostei and Holostei, formerly Ganoidei, and in the urodeles Ambystoma (Dempster, 1930) and Megalobatrachus japonicus (Sano and Imai, 19611, lymphohaemopoietic masses occur in association with the meninges and choroid plexuses of various regions of the central nervous system. According to our results, the histological organization of the lymphohaemopoietic tissue found in the meninges of the stingray Dasyatis akajei resembles that reported by light (Stahl, 1967;Fange and Sundell, 1969) and electron microscopy (Mattisson and Fange, 1986) for the cranial lymphoid tissues of holocephalans and for the lymphomyeloid aggregates present in the meninges of the fourth ventricle of ganoids (Chandler, 1911;Scharrer, 1944). In all these locations, a reticular stroma has been recognized where lymphoid cells and developing and mature granulocytes reside and differentiate.…”
Section: Discussionmentioning
confidence: 96%
“…It is therefore concluded that, like elasmobranchs (Hine & Wain 1987a, 1987b, 1987c many of the cells derive from the eosinophil lineage, but only the coarse granulocytes with their morphological, ultrastructural, and tinctorial similarities to eosinophils of higher vertebrates can be given a specific designation. The fine granulocytes, including lucent vesicle granulocytes (LVG), are ultrastructurally and enzyme cytochemically (Hine & Wain 1988) dissimilar to higher vertebrate granulocytes and the term "fine granulocyte" used by Fange & Sundell (1969) should be adopted.…”
Section: Discussionmentioning
confidence: 99%
“…In holocephalans granulocytopoiesis occurs in a creamy tissue in the wall of the orbit in association with a few lymphoid cells (Fange & Sundell 1969). Most lymphocyte development occurs in the large thymus and spleen.…”
Section: Introductionmentioning
confidence: 99%
“…In general, ovaries of C. callorhynchus exhibited the same features as other Chondrichthyes. As in other Holocephali, there was no evidence of an epigonal organ in C. callorhynchus (Bone & Moore, ; Fänge & Sundell, ). The maximum recorded follicle diameter was 49.3 mm.…”
mentioning
confidence: 99%